Fraud detection: An empirical study of publicly listed manufacturing in Indonesia (2020-2022) - B. Sundari, B. Sundari; L.R., Az Zahra; Budiasih, Budiasih (Jurnal Mantik, 2024)
Financial statements are the final result of the accounting process that contains company financial information presented to both internal and external parties. External parties such as investors use these financial statements as a tool in making investment decisions. Currently, many competing companies show improved performance through financial statements. The necessity to continue to make improvements and improve performance in order to get a good impression from various parties, especially investors, is one of the incentives that force company management to manipulate financial statements. This study aims to detect fraud or financial statement fraud with the influence of Nature of Industry, Change in Director, Frequent Number of CEO's Picture factors in manufacturing companies on the IDX (Indonesia Stock Exchange) for the 2020-2022 period, using the F-Score model. Method the data used is secondary data obtained from the company's financial and annual statements. This study used a purposive sampling technique obtained by 12 companies. The data analysis technique used in this study is logistics regression analysis using SPSS 25 software. The results of this study show that the variables External Pressure and Change in Auditor partially have a significant negative effect on the dependent variable. While Nature of Industry, Change in Director, Frequent Number Of CEO's Picture partially shows positive for the dependent variable. Simultaneously, all variables have a significant negative effect on financial statement fraud